2018
DOI: 10.1002/lt.25296
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopulmonary Syndrome in Children: A 20‐Year Review of Presenting Symptoms, Clinical Progression, and Transplant Outcome

Abstract: Hepatopulmonary syndrome (HPS) in stable patients with cirrhosis can easily be overlooked. We report on the presenting symptoms, disease progression, and outcomes after liver transplantation (LT) in children with HPS. Twenty patients were diagnosed with HPS between 1996 and 2016. The etiologies were as follows: biliary atresia (n = 9); alpha-1-antitrypsin deficiency (n = 2); cryptogenic liver disease (n = 3); and others (n = 6). HPS presentations were as follows; dyspnea (n = 17) and pneumonia (n = 3). For dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 16 publications
4
41
2
5
Order By: Relevance
“…The need for MV, the lengths of ICU and hospital stays, and the time required for weaning from supplemental O 2 were significantly longer in G2 than in G1. Similar to the results of other reports, 12,20,23,30…”
Section: Ta B L E 5 Group Comparison Of Outcome Datasupporting
confidence: 92%
See 2 more Smart Citations
“…The need for MV, the lengths of ICU and hospital stays, and the time required for weaning from supplemental O 2 were significantly longer in G2 than in G1. Similar to the results of other reports, 12,20,23,30…”
Section: Ta B L E 5 Group Comparison Of Outcome Datasupporting
confidence: 92%
“…Al‐Hussaini et al 12 and Warner et al 23 described supplemental oxygen therapy requirement in 55.5% and 69% of patients, respectively, in their series. In the present report, 47.5% of the patients required supplemental O 2 ; it should be noted that 80% of the patients with very severe hypoxemia were on O 2 therapy before transplantation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to certain postoperative complications after LT, including biliary leakage, PV thrombosis, and intracranial vascular complications, BASM syndrome–associated HPS appears to be another major cause of increased mortality in this cohort . Although some reports showed that HPS can improve after LT, the pathophysiology is still unknown, and patients with severe HPS in our patient series failed to improve their pulmonary situation. The overall number of BA patients with SI and HPS appears very limited, and the presentation of conclusive studies that provide guidelines for the indications of LT and, more importantly, valid thresholds to avoid inferior outcomes are, therefore, still lacking.…”
Section: Discussionmentioning
confidence: 71%
“…The mechanisms of hepatopulmonary syndrome are likely to involve endogenous vasodilators and pulmonary vascular remodeling. 4 Fifty years ago, the severe liver disease progressed slowly despite a thorough workup and this patient eventually developed a coma and died. Hepatopulmonary syndrome often resolves after liver transplantation and the availability of transplantation is the major difference from the situation 50 years ago.…”
mentioning
confidence: 98%